ENHANCEMENT OF ACTIVE POWER FLOW CAPACITY OF TRANSMISSION LINE USING SERIES COMPENSATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this paper a series controller from the FACTS (Flexible AC transmission system) family named as 'Thyristor Controlled Series Capacitor' (TCSC) is designed using Microcontroller. A transmission lines operating at high voltages is required to transmit power from generating station to load. The laboratory setup of circuit using a Thyristor controlled reactor in series with a capacitor will discussed in this paper. This paper also presents experimental results of a TCSC connected to a single phase system. This paper investigates the effects of TCSC on transmission line to improve voltage stability. The stability of system has been determined by using V-I and P-V curves.